مقارنة فاعلية بعض المساحيق الخاملة والنباتية والزيوت النباتية ضد خنفساء الخابرا Trogoderma granarium Everts وخنفساء الطحين الصدنية الحمراء Tribolium castaneum (Herbst) - الحديدي، إبراهيم خليل إبراهيم صالح (2013)
The present study compared the efficiency five types of inert dusts ; clay stone, marl, sulphur, dolomitic limestone, and sulphrous limestone and five types of plant powders and oils of five plants; Rosemary (Rosmarinus officinalis L.), Blackseed (Nigella sativa L.), Olive (Olea europaea L.), Marjoram (Origanum majoranum) and Blue gum (Eucalyptus sp.) against khapra beetle (Trogoderma granarium Everts) and red flour beetle (Tribolium castanium (Herbst)), and to study the effect of these dusts and oils on some biological aspects and mortality and population density of both beetles and their effect on reduction of loss in food medium mixed with them and their effect on planting percentage of wheat treated with them in which the inert dusts were mixed with wheat at concentrations 1, 3, 5, and 7g of inert dust/ kg of wheat, also the wheat was mixed with plant dusts at concentrations 3, 5, 7, and 9g of plant dust/ kg of wheat, while the plant oils were mixed with the wheat at concentrations 1.5, 3, 6, and 9% to study the aforementioned effects on khapra beetle, also the crushed partially debranned wheat was mixed with inert dusts and plant dusts and oils at aforementioned same concentrations to study their effects on red flour beetle. The results showed that the efficiency of inert dusts, plant powders and oils depended on dust or powder or oil type, mixture rate, beetle stage or species and exposure time. Sulphur dust showed significant superiority over the rest of dusts on mortality of both beetles which were 65.15 and 35.00% ,respectively. The rest of inert dusts graded according to their effect on khapra beetle mortality from highest to lowest mortality as follows; sulphrous limestone, dolomitic limestone, clay stone, and then marl , with respect to red flour beetle as follows; sulphrous limestone, clay stone, marl, and then dolomitic limestone. Marjoram powder showed significant superiority over the rest of plant powders on khapra beetle mortality and red flour beetle whereas blue gum powder showed significant superiority over the rest of the plant powders in exterminating red flour beetle which were 47.39 and 23.44% ,respectively, the rest of plant powders graded according to their effect on the average of the percentage of mortality khapra beetle from highest to the lowest as follows; Blue gum, Rosemary, Olive, and then Nigella powder. The other plant powders graded according to their effect on the average of the percentage of mortality red flour beetle from highest to the lowest as follows; Olive, Marjoram, Rosemary, and then Nigella powder. Adult khapra beetles were more sensitive to the inert dusts and plant powders than their third instar larvae whereas Sulphur dust caused mortality rate 89.16 and 41.04% ,respectively, and Marjoram powder caused mortality rate 80.83 and 13.95% ,respectively, while third instar larvae of red flour beetle were more sensitive than its adults to action of inert dusts and plant powders whereas sulphur dust caused mortality rate 43.75 and 26.25% ,respectively, and blue gum powder caused mortality rate 25.41 and 21.46% ,respectively. The results indicated that increment of used dust and powder concentration and exposure period caused increase of mortality for both beetles at all of used inert dusts and plant powders. Also inert dusts and plant powders caused larval stage period extension and emerging adults, laid eggs number and hatching percentage decrement and adult ages shortening but they did not effect on pupal stage and eggs incubation period for khapra beetle when the inert dusts and plant powders were mixed with wheat and for red flour beetle when they were mixed with crushed partially debranned wheat except rosemary powder which caused larval stage period shortening to red flour beetle about 1.51 day as compared with control, also sulphur dust and blue gum powder were most effective than other inert dusts and plant powders for both beetles. Also the results showed that population density for khapra beetle which were bred on wheat mixed with inert dusts and plant powders and for red flour beetle which were bred on crushed partially debranned wheat with inert dusts and plant powders at two storage periods its 3 and 6 months and also the loss percentage of wheat and crushed partially debranned wheat weights caused by feeding of feeding stages for both beetles under natural conditions of laboratory differed according to dust or powder type, mixture rate, beetle genus and storage period. The lowest average of total stages number summation rate caused by three pairs of khapra beetle breeding on wheat mixed with inert dusts was 38.2 individuals at sulphur dust and on wheat mixed with plant powder was 70.6 individuals at blue gum powder at 3 months from the storage it was encountered by a loss in wheat weight (0.69 and 1.26 g/100g of wheat) ,respectively. The lowest average of total stages number summation rate caused by three pairs of red flour beetle breeding on crushed partially debranned wheat mixed with inert dusts 27.1 individuals at sulphur dust on and crushed partially debranned wheat mixed with plant powder 51.58 individuals at blue gum at 3 months from storage it was encountered by a loss in crushed partially debranned wheat weight were 0.19 and 0.41 g/100g of crushed partially debranned wheat ,respectively, and 31.75 individuals at sulphur dust and 87.75 individuals at blue gum powder at 6 months from storage it was encountered by a loss in crushed partially debranned wheat weight were 0.51 and 1.42 g/100g of crushed partially debranned wheat ,respectively, the rest of inert dusts graded according to their effect on khapra beetle total stages number summation rate from the lowest to the highest rate as follows; sulphrous limestone, dolomitic limestone, marl, and then clay stone inert and for red flour beetle as follows; sulphrous limestone, marl, clay stone, and then dolomitic limestone. Also the rest of plant powders graded according to their effect on decreasing the average of the summation of the total stages for Khapra beetle from the lowest average to the highest one as follows; Marjoram, Rosemary, Olive, and then Nigella powder, and for red flour beetle as follows; Marjoram, Olive, Rosemary, and then Nigella powder. The results showed the significant superiority of blue gum oil over the other plant oils in mortality khapra beetle, the red flour beetle in which it caused a mortality percentage of 26.87 and 19.17%, respectively. Whereas the Nigella oil showed the lowest percentage of mortality beetle (17.92%). The other plant oils graded in their effect on the mortality percentage average from the highest to the lowest as follows; Olive, Marjoram, and then Rosemary oil. As for Rosemary, it showed the lowest average of mortality red flour beetle (4.79%). The other plant oils graded in their influence on the average of mortality the red flour beetle from the highest to the lowest as follows; Blue gum, Marjoram, and then Nigella oil. The adult insects of khapra beetle were more influenced by the plant oils than the third instar larvae in which the average of the percentage of mortality caused by blue gum was 47.28% and 6.46% , respectively. It was noted that the increase in the concentration of the oil used and the increased exposure caused an increase in percentage of mortality of both insects by all the plant oils used. The plant oils prolonged the larval stage and decreased the number of the outgoing insects, the eggs laid by each female insect, the percentage of egg hatching, and they decrease the age of the adult insects. Nevertheless, they did not affect the periods of pupal stage and eggs incubation of khapra beetle in wheat and red flour beetle in crushed partially debranned wheat. Blue gum oil prolonged the pupal stage period whereas the nigella oil significantly decreased the pupal stage period of red flour beetle. Blue gum oil as compared with the other plant oils, was the most effective one on the biological aspects of the two insects. Results showed that the lowest average of the summation of total stages number of three pairs of khapra beetle grown among wheat treated by plant oils was 52.33 individual for blue gum at three months of storing it was encountered by a lack of wheat weight (0.75g/100g of wheat) and 144.83 individual for the same oil at six months of storing which was encountered by a lack of wheat weight (2.10g/ 100g of wheat). The rest of plant oils graded in their effect on decreasing the average of the summation of total stages number of khapra beetle from the lowest average to the highest one as follows; Marjoram, Olive, Nigella, and then Rosemary oil. The lowest average of the summation of total stages number of three pairs of red flour beetle grown among crushed partially debranned wheat treated with plant oils was 53.33 individual for blue gum oil at three months of storing which was encountered by a loss of crushed partially debranned wheat weight (0.39g/100g of crushed partially debranned wheat) and 75.83 individual for the same oil at six months of storing. It was encountered by a loss of crushed partially debranned wheat weight (1.11g/100g of crushed partially debranned wheat). The other plant oils graded in their effect on decreasing the average of the summation of total stages number of red flour beetle from the lowest average to the highest one as follows; Olive, Marjoram, Nigella, and then Rosemary oil.